Optimizing prognosis in atrial fibrillation: A call to action in Portugal - Ferreira, Jorge (2021)
Atrial fibrillation (AF), the most common arrhythmia in the adult population worldwide, represents a significant burden in terms of cardiovascular mortality and morbidity and has repercussions on health economics. Oral anticoagulation (OAC) is key to stroke prevention in AF and, in recent years, results from landmark clinical trials of non-vitamin K oral anticoagulants (NOAC) have triggered a paradigm shift in thrombocardiology. Despite these advances, there is still a significant residual vascular risk associated with silent AF, bleeding, premature sudden death and heart failure. The authors review AF epidemiologic data, the importance of new tools for early AF detection, the current role of catheter ablation for rhythm control in AF, the state-of-the-art in periprocedural OAC, the optimal management of major bleeding, the causes of residual premature death and future strategies for improvements in AF prognosis.